DR DARKO DIMOVSKI "ETIOLOGY OF CRIME", CENTER FOR PUBLICATIONS, FACULTY OF LAW, UNIVERSITY IN NIS, NIS, 2019 - Mirić, Filip (COLLECTION OF PAPERS, FACULTY OF LAW NIŠ, 2019)
The need to study the causes of crime has existed since the existence of organized social communities. Namely, people have always been interested in what causes people’s criminal behavior and how it can be prevented. From these aspirations a criminal etiology emerged, as part of Criminology. On the other hand, knowledge of the causes and causes of crime, as a mass social phenomenon and as individual behavior, contributes to the design of effective measures for its prevention and suppression. This is especially significant due to crime, in the times we live in, is manifesting itself in increasingly complex forms with grave consequences.Criminal etiology is a central field of study in Criminology. It deals with the study of the causes, conditions and causes of criminal behavior. It is inextricably linked to criminal phenomenology because crime as an antisocial phenomenon, cannot be analyzed and understood without knowing its causes. Therefore, crime research must be approached interdisciplinarily. Prof. dr. Dr. Darko Dimovski, in his monograph "Criminal Etiology", analyzes crime in this way, and this monograph is an extremely important analytical and synthetic study of the most important criminological theories and factors of criminality. Contemporary Serbian criminological literature lacks studies on criminal etiology, which is why this monograph is important.